A gold-nanodot-decorated hollow carbon nanosphere based nanoplatform for intracellular miRNA imaging in colorectal cancer cells. Issue 82 (27th September 2019) - Xiao, Heng; Fan, Huiling; Xu, Luming; Pei, Zhiyin; Lei, Shijun; Xu, Jinglei; Xi, Jiangbo; Wang, Guobin; Wang, Lin; Wang, Zheng
Abstract : We report a new biofunctionalized nanoplatform based on hyaluronic acid-coated gold-nano-dot-decorated hollow carbon nanospheres (AuHCNs-HA) for microRNA imaging in living cells. Abstract : We report a new biofunctionalized nanoplatform based on hyaluronic acid-coated gold-nano-dot-decorated hollow carbon nanospheres (AuHCNs-HA) for microRNA imaging in living cells. Importantly, the HA-coated nanoplatform could be internalized into target cells via CD44 receptor-mediated endocytosis. It can be further applied for intracellular miR-21 imaging in CD44-positive colorectal cancer cells.